2017
DOI: 10.1111/trf.14289
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis related to intravenous immunoglobulins is dependent on the presence of anti‐blood group A and B antibodies and individual susceptibility

Abstract: BACKGROUND Patients treated with intravenous immunoglobulins (IVIG) rarely experience symptomatic hemolysis. Although anti‐A and anti‐B isoagglutinins from the product are involved in most cases, the actual mechanisms triggering hemolysis are unclear. STUDY DESIGN AND METHODS A prospective, open‐label, multicenter, single‐arm clinical trial in 57 patients with immune thrombocytopenia treated with IVIG (Privigen, CSL Behring) was conducted. RESULTS Twenty‐one patients received one infusion (1 g/kg) and 36 recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…More recent studies have confirmed the differences in IVIG‐associated HE risk between blood groups and refined the risk estimate within blood groups. Mielke et al found a correlation between blood group antigen density on erythrocytes and HE risk, with a higher risk in blood group A1 versus A2 . A genotyping study found a trend toward HE risk mitigation by the O allele, with a lower risk in AO and BO versus AB , AA , and BB genotypes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have confirmed the differences in IVIG‐associated HE risk between blood groups and refined the risk estimate within blood groups. Mielke et al found a correlation between blood group antigen density on erythrocytes and HE risk, with a higher risk in blood group A1 versus A2 . A genotyping study found a trend toward HE risk mitigation by the O allele, with a lower risk in AO and BO versus AB , AA , and BB genotypes .…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous immunoglobulin (IVIG) is widely used in the treatment of primary and secondary immunodeficiencies, as well as for immunomodulatory treatment in autoimmune diseases, including immune thrombocytopenia, Guillain Barré syndrome, chronic inflammatory demyelinating polyneuropathy, and Kawasaki disease . Hemolytic events (HEs) are a known but rare adverse effect of IVIG therapy, for which risk factors include high IVIG dose (e.g., ≥2 g/kg body weight), patient blood group, and underlying inflammatory state . With regard to blood group, there is a type‐specific hierarchy of HE risk: AB > A > B > O .…”
mentioning
confidence: 99%
“…As these preparations are made from pooled donors preferably from patients with blood group O, there are chances of the creeping in of anti-A, anti-B, and sometimes anti-D or other red blood cells (RBCs) antibodies in the product during the preparation. The problem that arises because of these constituents of IVIG is hemolysis, although it is usually reported with very high dose and in patients with blood group A, AB, or B [11]. Such conditions are also reported to have occurred more frequently in persons with reduced bone marrow reserve or post hemopoietic stem cell transplantation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous literature and manufacturer leaflets have suggested that serious forms of hemolysis only occur with a very high dose or repeated courses of IVIG treatment, we found that given the susceptibility of the person, he or she is liable to have hemolysis even with low dose treatment of IVIG. Thus, individual susceptibility to hemolysis plays a significant role [11]. We may, however, surmise that our anecdotal experience may require further validation.…”
Section: Discussionmentioning
confidence: 99%
“…). Repeat testing 1 week later showed an A2‐IgG titer of 256; however, this was after administration of IVIG (2 g/kg), which also contains ABO antibodies that have been variably associated with hemolysis . Antimicrobial therapy for his wound infection precluded additional immunosuppressive therapy for rejection for another week.…”
mentioning
confidence: 99%